Effects of dietary phospholipids on growth, biochemical composition, fatty acid profiles, blood metrics, and sex steroid hormone of male pangasius nasutus broodstock - Donald Torsabo; Nurizzati Idris; Benedict Terkula Iber; Ataguba Gabriel Arome; Ivan Koh Chong Chu; Muhammad Yazed Abduh; Noordiyana Mat Noordin; Mohamad Nor Azra; Federica Impellitteri; Caterina Faggio; Ambok Bolong Abol-Munafi (Central Fisheries Research Institute (SUMAE), 2025)
This study investigates the effects of phospholipids (PLs) supplemented diets on the growth, blood metrics, reproductive indices, and fatty acid profiles of male Pangasius nasutus (shark catfish) broodstock, a commercially valuable freshwater fish species. Over a 90-day feeding trial, four groups of fish were placed in a large open earthen pond within 4 cages with a control group. Each cage housed 15 fish, with an initial average weight of 643±0.34g and an average length of 43.3±0.12 cm. These fish were fed different levels of PLs (0, 1.5, 2, and 2.5%) in their diets twice daily, at 700 am and 600 pm, to satiation. The results showed that PLs supplementation significantly improved some of the biological indices, such as hepatosomatic index, coelomic fat index, feed conversion ratio, and survival rate. PLs supplementation also influenced the blood metrics, such as red blood cell count, hematocrits, hemoglobin, and white blood cell count. PLs supplementation significantly improved reproductive indices, including GSI, elevated 11-ketotestosterone production, and altered fatty acid profiles in male P. nasutus. These findings suggest PLs potential to enhance reproductive performance and fish nutrition, both of which are critical to aquaculture production.